1974
DOI: 10.1002/neu.480050404
|View full text |Cite
|
Sign up to set email alerts
|

The in vitro polymerization of tubulin from beef brain

Abstract: SUMMARYThe conditions for the in uitro polymerization of beef brain tubulin have been examined using turbidity and electron microscopic examination as methods of following the reaction. The optimal conditions are 37"C, pH 6.0-6.4, and an ionic strength of approximately 0.08 t o 0.1 p . The ionic strength is particularly critical, a t 0.25 p the polymerization does not occur and increasing the ionic strength of a solution containing microtubules to this value causes the tubules to depolymerize. GTP and Mg2+ are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

1974
1974
1996
1996

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(32 citation statements)
references
References 19 publications
1
31
0
Order By: Relevance
“…The viscosity of the tubulin fraction typically showed a transient rise at approximately 5 min followed by a rapid decline to baseline levels. After [20][21][22][23][24][25][26][27][28][29][30] (2) Sedimentation. Following incubation at 37°for 30 min, we assayed 0.5 ml aliquots of the same samples by sedimentation to determine the extent of polymerization.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The viscosity of the tubulin fraction typically showed a transient rise at approximately 5 min followed by a rapid decline to baseline levels. After [20][21][22][23][24][25][26][27][28][29][30] (2) Sedimentation. Following incubation at 37°for 30 min, we assayed 0.5 ml aliquots of the same samples by sedimentation to determine the extent of polymerization.…”
Section: Methodsmentioning
confidence: 99%
“…Purified microtubule protein was obtained from porcine brain tissue by two cycles of a reversible temperature-dependent assembly procedure (10). Protein was prepared at 00 in polymerization medium (PM) [0.1 M piperazine-N,N'-bis(2-ethanesulfonic acid) (Pipes) adjusted with NaOH to pH 6 Since monovalent cation concentrations above 0.2 M inhibit microtubule assembly (16,21), it was necessary to remove the salt from the purified fractions before assaying them for polymerization. When purified tubulin (0.8 M KCI fraction) was desalted and brought up to 370 in PM containing 1.0 mM GTP, viscometry and sedimentation showed that little polymerization occurred at protein concentrations as high as 4.0 mg/ml.…”
Section: Methodsmentioning
confidence: 99%
“…4b) as the previous control. Cooling to O' will not depolymerize the fixed microtubules, indicating they are chemically crosslinked, since cooling of untreated microtubules readily reverses polymerization (10). After pressure treatment at 5000 lbs./inchl for 45 min, the tubules' appearance suggests that they are more flexible ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Tubulin, the protein subunits of the microtubules, will quickly polymerize to form microtubules within 1-2 min under optimal conditions and can be followed by spectrophotometric changes at 500 nm (10). No Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation